Financial Pressures and Earnings Management: Evidence from Capital-Intensive Firms in Indonesia - Restiana Ie Tjoe Linggadjaya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
This study examines how financial pressures, reflected through tax aggressiveness, capital intensity, leverage, and revenue growth on earnings management in capital-intensive industries, particularly those operating in Indonesia’s basic materials sector. The basic materials sector is highly sensitive to fiscal pressure and commodity price volatility, making firms more vulnerable to earnings manipulation. Existing studies have examined, yet limited research analyzes within a capital-intensive context, especially in Indonesia. This study fills the gap by providing empirical evidence using 65 firms with 325 yearly observations from 2019 to 2023 through multiple linear regression. The findings reveal that capital intensity negatively affects earnings management in high-capital-intensity industries. In contrast, leverage and revenue growth positively affect earnings management. Our findings also reveal that aggressive tax strategies do not result in earnings management. These findings deepen the scholarly understanding of financial conduct within capital‑intensive industries and highlight the critical role of underlying determinants in shaping earnings management practices, in the midst of regulatory oversight and corporate governance, in reducing financial reporting errors. Future research should add moderating and mediating factors, such as ownership and corporate governance variables, which might influence earnings management. Also, to enlarge the scope in other sectors across ASEAN countries to facilitate generalizability to a wider population.